Cisplatin-based chemotherapy for the treatment of metastatic collecting duct carcinomas: A real-world, retrospective analysis - Rizzo, Mimma; Chiellino, Silvia; Gernone, Angela; Porta, Camillo (Frontiers in Oncology, 2022)
Collecting duct carcinomas (CDCs) are a particularly rare subtype of kidney cancer, endowed by a particularly poor prognosis. Since no active treatments have been established for CDCs, due to similarities with upper tract urothelial carcinomas, the use of the cisplatin-gemcitabine doublet has been the standard of care for decades. Here we report a retrospective analysis of 36 metastatic CDCs treated, as everyday clinical practice, with either cisplatin-gemcitabine or cisplatin-gemcitabine-paclitaxel from 2005 to 2021. Thirty-three patients received gemcitabine (1000 mg/m2, days 1 and 8) and cisplatin (70 mg/m2, day 1), while 3 were treated with paclitaxel (80 mg/m2, days 1 and 8), gemcitabine (1000 mg/m2, days 1 and 8) and cisplatin (70 mg/m2, day 1), every 21 days for a maximum of 6 cycles. Eight out of 36 patients (22.2%) experienced a partial response, while 9 others (25%) had a disease stabilization. Notably, no benefit was observed in patients treated with the triplet. Median PFS was just 6 months, while median OS was 8 months. The commonest grade ≥3 treatment-related adverse events were: neutropenia (75%, 11.1% of febrile neutropenia), anemia (50%), thrombocytopenia (38.8%), and vomiting (8.3%). Dose omissions and dose reductions were common, and few frail patients started the treatment with a 25% dose reduction. In conclusion, our real-world experience confirmed the modest activity and relevant toxicity of cisplatin-based chemotherapy for the treatment of CDCs. More translational studies and novel study designs are thus badly needed in these still orphan tumors.